There, we explained the terms Factors or Divisors, Factorization of Polynomials, Prime Polynomial etc.
That knowledge is a prerequisite here.
Here, we factorize higher degree ( > 2 ) polynomials using Factor Theorem which is based on Remainder Theorem.
If a Polynomial in x, say f(x) is divided by (x - a), then the remainder is f(a).
Proof : We know Dividend = Divisor x Quotient + Remainder Let q(x) be the Quotient and r be the Remainder when f(x) is divided by (x - a). Then we have f(x) = (x - a) x q(x) + r where in the degree of q(x) is one less than that of f(x) and r is a constant. Since the equation is true for all real values of x, putting x = a in the equation, we get f(a) = (a - a) x q(a) + r = 0 + r = r ⇒ r = f(a). Thus, when f(x) is divided by (x - a), the remainder is f(a). (Proved.) Note:
If f(x) is divided by (ax + b), then the remainder is f(-b ⁄a)
The proof for this is similar to the one given above.
Example on Remainder Theorem : Factoring Polynomials
Find the remainder when 3x3 - 2x2 + x + 2 is divided by (i) x - 1 (ii) x + 2 (iii) 2x -1 (iv) 3x + 2
Solution: Let f(x) = 3x3 - 2x2 + x + 2 (i) when f(x) is divided by (x - 1), The remainder = f(1) = 3(1)3 - 2(1)2 + (1) + 2 = 3 - 2 +1 + 2 = 4. Ans. (ii) when f(x) is divided by (x + 2), The remainder = f(-2) = 3(-2)3 - 2(-2)2 + (-2) + 2 = 3(-8) - 2(4) - 2 + 2 = -32. Ans. (iii) when f(x) is divided by (2x -1), The remainder = f(1⁄2) = 3(1⁄2)3 - 2(1⁄2)2 + (1⁄2) + 2 = 3(1⁄8) - 2(1⁄4) + 1⁄2 + 2 = (3 - 2 x 2 + 1 x 4 + 2 x 8)⁄8 = 19⁄8 Ans. (iv) when f(x) is divided by (3x + 2), The remainder = f(-2⁄3) = 3(-2⁄3)3 - 2(-2⁄3)2 + (-2⁄3) + 2 = 3(-8⁄27) - 2(4⁄9) - 2⁄3 + 2 = (3 x -8 - 2 x 4 x 3 - 2 x 9 + 2 x 27)⁄27 = -12⁄27 = -4⁄9 Ans.
An important application of Remainder Theorem is the Factor Theorem which is applied in Factoring polynomials.
Factor Theorem : Factoring Polynomials
We know that, if the remainder is zero, when a Polynomial f(x) is divided by (x - a), then (x - a) is a factor of f(x). But, as per remainder theorem, remainder = f(a). ∴ If f(a) = 0, then (x - a) is a factor of f(x). Also If (x - a) is a factor of f(x), then f(a) = 0. This is Factor theorem.
(x - a) is a factor of f(x) ⇔ f(a) = 0
Factor Theorem is very useful in Factoring Polynomials of higher (than 2) degree .
Get The Best Grades With the Least Amount of Effort
Here is a collection of proven tips, tools and techniques to turn you into a super-achiever - even if you've never thought of yourself as a "gifted" student.
The secrets will help you absorb, digest and remember large chunks of information quickly and easily so you get the best grades with the least amount of effort.
If you apply what you read from the above collection, you can achieve best grades without giving up your fun, such as TV, surfing the net, playing video games or going out with friends!
Method of Factoring Polynomials using Factor Theorem :
The method of Factoring Polynomials involves the following steps.
STEP 1: Let the Polynomial be f(x). Check whether (x- a) is a factor of f(x) or not. To check whether (x - a) is a factor of f(x) or not, we have to checkwhether f(a) is zero or not. Choosing values of a is done by trial and error.To facilitate, reducing the number of trials, we take the constant termof the Polynomial, f(x), find its factors, put + and - to the factors and takethose values for a and check with them, if f(a) is zero or not. This isdone till we find an a such that f(a) is zero. STEP 2: After deciding (x - a) is a factor, we divide the Polynomial f(x) by (x - a) to get the Quotient. This division is better done by Synthetic Divisionwhich is explained in Solved Example 1 of Set 3 below. STEP 3: we, then Factorize the Quotient for further factors. This Factorizingis done either by Factor theorem (Repeat from Step 1) or by other methodsdepending upon the degree of the Quotient.
The method of Factoring Polynomials will be clear by the following set of Solved Examples.
Example 1 of Factoring Polynomials
Solve the following problem on Factoring Polynomials
If a and b are unequal and x2 + ax + b and x2 + bx + a have a common factor,show that a + b + 1 = 0
Solution to Example 10 of Factoring Polynomials
Let f(x) = x2 + ax + b; and p(x) = x2 + bx + a Let (x - k) be the common factor of f(x) and p(x).⇒ f(k) = 0 and p(k) = 0 f(k) = 0 ⇒ k2 + ak + b = 0............(i) p(k) = 0 ⇒ k2 + bk + a = 0............(ii) (i) - (ii) gives (k2 + ak + b) - (k2 + bk + a) = 0 - 0 = 0 ⇒ ak + b - bk - a = 0 ⇒ k(a - b) -1(a - b) = 0 ⇒ (a - b)(k- 1) = 0 ⇒ ( (k- 1) = 0 [ Since by data a and b are unequal ⇒ (a - b) ≠ 0 ] ⇒ k = 1. Substituting this value of k in (i), we get (1)2 + a(1) + b = 0 ⇒ a + b + 1 = 0 Thus, If a and b are unequal and x2 + ax + b and x2 + bx + a have a common factor,we could show that a + b + 1 = 0 using Factor Theorem in Factoring polynomials.
Solve the Following Problems on Factoring polynomials :
If f(x) = x2 + 5x + a and p(x) = x2 + 3x + b have a common factorthen (i) find the common factor (ii) show that (a - b)2 = 2(3a - 5b)
For Answer See at the bottom of the Page.
Progressive Learning of Math : Factoring Polynomials
Recently, I have found a series of math curricula (Both Hard Copy and Digital Copy) developed by a Lady Teacher who taught everyone from Pre-K students to doctoral students and who is a Ph.D. in Mathematics Education.
This series is very different and advantageous over many of the traditional books available. These give students tools that other books do not. Other books just give practice. These teach students “tricks” and new ways to think.
These build a student’s new knowledge of concepts from their existing knowledge. These provide many pages of practice that gradually increases in difficulty and provide constant review.
These also provide teachers and parents with lessons on how to work with the child on the concepts.
The series is low to reasonably priced and include